Penyuluhan SSDI sebagai Upaya Meningkatkan Pengetahuan, Keterampilan dan Kesadaran Ibu dalam Menstimulasi Anak Usia Dini di Rusunawa Jatinegara Kaum Jakarta Timur - Kahdafi, Delinia; Salsabila, Arfina Syifa; Rizqianni, Linda Khoiri; Fahmi , Tahnia Nazlan; Kabbaro, Hurriyyatun (EDUPEDIA Publisher, 2024)
The period 0-6 years is usually known as the golden age in child development. At this age, children experience rapid development, both physically, cognitively, socially and emotionally. Therefore, it is important to provide appropriate stimulation for children so that their development is optimal. Parents have a strategic role in stimulating early childhood development. This activity aims to increase the number of parents who have knowledge about early childhood stimulation in order to optimize their children's potential. Researchers collaborate with BKB PAUD Cahaya Permata. This activity was carried out at BKB PAUD Cahaya Permata located at Rusunawa Jatinegara Kaum Block A, Ground Floor, RT. 001 RW. 009, East Jakarta with a population of 12 parents of BKB PAUD Cahaya Permata students. Extension using lecture, discussion and demonstration methods to stimulate children which involves the active role of parents of toddlers. The results show that there has been an increase in the number of parents who have knowledge about early child stimulation and an increase in the average level of parental knowledge by 12.34% from 61.66% to 74%. After counseling and stimulating children, parents can understand the urgency and stimulation of children from an early age.